Burn It or Return It? The Effects of the Possibility to Return Budget Surplus and the Moderating Role of Uncertainty on Capital Budgeting - Arnold, Markus C.; Bauch, Kai A.; Elsinger, Florian (The Accounting Review, 2026)
ABSTRACT We conduct two experiments to investigate the effects of giving subordinates the possibility to return budget surplus on capital budgeting processes. We predict and find that when subordinates face low uncertainty when submitting their budget request, the possibility to return budget surplus increases budget requests compared to not having this possibility but that this effect is mitigated under high uncertainty. We also predict and find that subordinates return more budget surplus under high than low uncertainty. Together, these results imply that the possibility to return budget surplus can be particularly beneficial for firms operating under high uncertainty. We contribute to the literature by integrating an important feature of budgeting practice into research, i.e., subordinates’ possibility to return budget surplus and by showing that the effects of implementing such an option may strongly depend on the level of uncertainty a subordinate faces. Data Availability: The data and research instrument are available from the authors upon request. JEL Classifications: D91; M10; M40.